Cultural Design - Gumelar, Michael Sega (An1mage Jurnal Studi Kultural, 2017)
Cultural is a construction runs on an ongoing basis from a bad to a better direction from and for humans in an environment to achieve prosperity, happiness and peace of all people in an area. Clash of cultural is a necessity that is inevitable in the era of information and globalization. There is a strong cultural dominance in globalization to imply a false consciousness to the younger generation and its hegemonic. Even some people being hegemony information slaves (hegeformaslaves) by cultural and sadly they do not even realised it. There is a cultural resistance, adaptation, and acculturation occur. When thinking about the need for a strong cultural identity, the need for redigging, reshaping, and finding again the ancestral identity to be used as construction of new cultural identities as a unifying with the goal of unity, prosperity, happiness and peace in a community.   This globalization era required a local merger with global thought that does not cancel each other out, but belong together and complete it. Thinking "local go global" resulting in a mix of local and global (Locglo). Instead of thinking global-local (Glocal), global tends to intimidate and repress local in the sense that the main priority is global and not local. Locglo is thought that promotes local equivalent to the global. Dayak in the need of reconstructing a better cultural identity requiring comparative studies with people on the island of Bali that measures future construction design thinking this culture can be projected and used as a cultural construction for the Dayak's new better culture based on humanity and speciesity in achieving the noble values of the ancestors of togetherness, welfare, and peace for Dayak locally and globally.